Insights into the structure of mature streptavidin C1 from Streptomyces cinnamonensis reveal the self-binding of the extension C-terminal peptide to biotin-binding sites - Byeong Jun Jeon; Sulhee Kim; Min-Seok Kim; Ji-Ho Lee; Beom Seok Kim; Kwang Yeon Hwang (IUCrJ, 2021)
The members of the avidin protein family are well known for their high affinity towards d-biotin and their structural stability. These properties make avidins a valuable tool for various biotechnological applications. In the present study, two avidin-like biotin-binding proteins (named streptavidin C1 and C2) from Streptomyces cinnamonensis were newly identified while exploring antifungal proteins against Fusarium oxysporum f. sp. cucumerinum. Streptavidin C1 reveals a low correlation (a sequence identity of approximately 64%) with all known streptavidins, whereas streptavidin C2 shares a sequence identity of approximately 94% with other streptavidins. Here, the crystal structures of streptavidin C1 in the mature form and in complex with biotin at 2.1 and 2.5 Å resolution, respectively, were assessed. The overall structures present similar tetrameric features with D2 symmetry to other (strept)avidin structures. Interestingly, the long C-terminal region comprises a short α-helix (C-Lid; residues 169–179) and an extension C-terminal peptide (ECP; residues 180–191) which stretches into the biotin-binding sites of the same monomer. This ECP sequence (–180VTSANPPAS188–) is a newly defined biotin-binding site, which reduces the ability to bind to (strept)avidin family proteins. The novel streptavidin C1 could help in the development of an engineered tetrameric streptavidin with reduced biotin-binding capacity as well as other biomaterial tools.